Training needs for research in health inequities among health and demographic researchers from eight African and Asian countries - Haafkens, Joke; Becher, Heiko; Ramroth, Heribert (BMC public health, 2014)
To support equity focussed public health policy in low and middle income countries, more evidence and analysis of the social determinants of health inequalities is needed. This requires specific know how among researchers. The INDEPTH Training and Research Centres of Excellence (INTREC) collaboration will develop and provide training on the social determinants of health approach for health researchers from the International Network for the Demographic Evaluation of Populations and Their Health in Low- and Middle-Income Countries (INDEPTH) in Africa and Asia. To identify learning needs among the potential target group, this qualitative study explored what INDEPTH researchers from Ghana, Tanzania, South Africa, Kenya, Indonesia, India, Vietnam, and Bangladesh feel that they want to learn to be able to conduct research on the causes of health inequalities in their country.
Gesehen am 20.10.2020